PENINGKATAN HASIL BELAJAR LUAS TRAPESIUM DAN LAYANG- LAYANG DENGAN MODEL COOPERATIVE LEARNING TIPE STAD DI SEKOLAH DASAR - Dewi, Afrisma (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2013)
This study aimed to describe the planning, execution, and improved learning outcomes trapezoidal broad flat wake and kite in class V SD Negeri 16 Campago Ipuh Bukittinggi. The method used the cooperative model type Student Teams Achievement Divisions (STAD). The approach used in this study is a qualitative approach. Data collected through observation, testing, and observation sheets. The results obtained in this finding RPP 93%, 92.86% implementation, students' cognitive aspects of 85.47, 85.28 and affective aspects of psychomotor aspects of 85.22 in the second cycle Kata kunci  :  hasil  belajar,luas trapesium dan layang-layang, model  cooperative       learning: (stad)